2014
DOI: 10.1080/00207144.2014.901055
|View full text |Cite
|
Sign up to set email alerts
|

Hypnobehavioral and Hypnoenergetic Therapy in the Treatment of Obese Women:A Pragmatic Randomized Clinical Trial

Abstract: This study compared the effectiveness of hypnobehavioral therapy (HypBe) and HypBe enhanced by elements of energetic psychotherapy (hypnoenergetic therapy, HypEn) for obese women. Sixty clients were randomized to either HypBe or HypEn. Body weight, BMI, eating behavior, and body concept were assessed at baseline, posttreatment, and at a follow-up. Mixed ANOVA models and effect sizes were used for statistics. Both treatments improved weight, BMI, eating behavior, and some aspects of body concept. Improvements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Hypnosis has been reported to be successful, not by itself as a treatment for obesity but as a facilitator of a specific lifestyle intervention by increasing patient involvement in the therapeutic process (). Therefore, hypnosis has usually been combined with behavioral approaches, and most of these treatments are long‐lasting, complex, challenging, and, therefore, difficult to perform routinely ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypnosis has been reported to be successful, not by itself as a treatment for obesity but as a facilitator of a specific lifestyle intervention by increasing patient involvement in the therapeutic process (). Therefore, hypnosis has usually been combined with behavioral approaches, and most of these treatments are long‐lasting, complex, challenging, and, therefore, difficult to perform routinely ().…”
Section: Discussionmentioning
confidence: 99%
“…The hypnotic procedure has varied greatly among studies. The following methods have been used: a 9‐week program, with the presentation of eating and dieting rules during the hypnotic sessions (); the utilization of audiotapes after the hypnotic treatment with a therapist (); the combination of hypnotic and behavioral therapy for 12 sessions over a period of 8.5 months (); and a multifaceted program with suggestions for relaxation, self‐control, and self‐esteem, strengthening motivation toward change (). Most of these treatments are long, demanding, and difficult to perform in clinical practice on a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy the dropout rate was 25% [ 43 ], thus requiring caution in the interpretation of these results. In 2014, two types of hypnotherapies were compared in 60 females with obesity by a parallel RCT: hypno-behavioral therapy (HypBe) (a combination of hypnotherapy—i.e., hypnotic trances—plus behavioral therapy—i.e., behavioral exercises, role-playing, and homework) and hypno-energetic (HypEn) therapy (a therapy enhancing the hypno-behavioral strategies with acupressure, that is, the manual stimulation of acupuncture in the related points) [ 44 ]. Both treatments consisted of 12 sessions lasting 120 min over an 8.5-month period, and participants were assessed at the beginning and the end of the treatment, as well as after 6-month follow-up.…”
Section: Hypnosismentioning
confidence: 99%
“…Both treatments consisted of 12 sessions lasting 120 min over an 8.5-month period, and participants were assessed at the beginning and the end of the treatment, as well as after 6-month follow-up. Regardless of the hypnotherapy received, initial weight and BMI were significantly reduced from the beginning to the end of treatment (−2.4 kg, p <0.01 and −0.8 kg/m 2 , p <0.01 within the HypBe group; −3.1 kg, p <0.01 and −1.1 kg/m 2 , p <0.01 within the HypEn group), but significant weight and BMI reductions from the end of treatment to the follow-up (−2.2 kg, p <0.01 and −0.8 kg/m 2 , p <0.01) and significant improvements in eating behaviors, and several aspects of body concept, such as physical efficiency, self-acceptance of the body/physical appearance/sexuality, were observed in the HypEn group only [ 44 ]. A systematic review of 5 meta-analyses of RCTs demonstrated the efficacy of medical hypnosis in the reduction of pain and emotional stress during medical interventions (34 RCTs, 2597 patients) [ 45 ].…”
Section: Hypnosismentioning
confidence: 99%
See 1 more Smart Citation